The Impact of Tax Incentives on Foreign Direct Investment in Indonesia - Rotua Andriyati Siregar; Arianto Patunru (Journal of Accounting Auditing and Business, 2021)
Using the data from twenty-two partner countries in 1999 to 2018, this paper presents the impact of tax incentives on foreign direct investment (FDI) in Indonesia. A fixed-effect and least square dummy variable analysis are used to determine the direction and significance of tax incentives in its correlation with FDI together with other FDI determinant. The main finding shows that as tax incentives increase, the FDI flow decrease significantly. However, corporate income tax (CIT) rate which also used as investment cost proxy shows that as it decreases the FDI flow will increase.